2013
DOI: 10.1007/s10495-013-0889-4
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of boswellic acid analog BA145 induced caspase dependent apoptosis by PI3K inhibitor LY294002 and MEK inhibitor PD98059

Abstract: PI3K/Akt and ERK pathways are important for growth and proliferation of many types of cancers. Therefore, PI3K inhibitor LY294002 (LY) and MEK1/2 inhibitor PD98059 (PD) are used to sensitize many types of cancer cell lines to chemotherapeutic agents, where AKT and ERK pathways are over activated. However, in this study, we show for the first time that PD could protect the leukemia cells independent of ERK pathway inhibition, besides, we also report a detailed mechanism for antiapoptotic effect of LY in HL-60 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…It is also well known that agents induced apoptosis via caspase‐dependent and ‐independent pathways (Pathania et al, ; Chen et al, ), herein, our results from Figure (A–C) indicated that α‐PA promoted the activities of caspase‐8, −9, and −3. On the basis of these observations, we suggested that α‐PA induced apoptosis in WEHI‐3 cells through the caspase‐dependent pathway.…”
Section: Resultssupporting
confidence: 75%
“…It is also well known that agents induced apoptosis via caspase‐dependent and ‐independent pathways (Pathania et al, ; Chen et al, ), herein, our results from Figure (A–C) indicated that α‐PA promoted the activities of caspase‐8, −9, and −3. On the basis of these observations, we suggested that α‐PA induced apoptosis in WEHI‐3 cells through the caspase‐dependent pathway.…”
Section: Resultssupporting
confidence: 75%
“…At present, Mcl‐1 is an attractive target for novel gene therapy strategies in different types of carcinomas and has been related to anti‐apoptosis and increased resistance to chemotherapy in human malignancies . Some studies have shown that expression of Mcl‐1 is regulated by the JAK/STAT, MAPK and PI‐3K signaling pathways and that these signaling pathways are distinct from other signal transduction pathways for the regulation of cell stress, growth, proliferation, differentiation and apoptosis . Moreover, Mcl‐1 knockdown induces cell apoptosis after inhibition of the pro‐survival JAK/STAT, MAPK and PI‐3K signaling pathways .…”
mentioning
confidence: 99%
“…Some studies have shown that expression of Mcl‐1 is regulated by the JAK/STAT, MAPK and PI‐3K signaling pathways and that these signaling pathways are distinct from other signal transduction pathways for the regulation of cell stress, growth, proliferation, differentiation and apoptosis . Moreover, Mcl‐1 knockdown induces cell apoptosis after inhibition of the pro‐survival JAK/STAT, MAPK and PI‐3K signaling pathways . However, the signaling pathways that influence Mcl‐1 expression after MTB infection have not been studied.…”
mentioning
confidence: 99%
“…Protein content was measured by Bradford reagent (Bio-Rad) and 30–70 µg protein amount were run by using SDS-PAGE followed by western blotting as described earlier [17].…”
Section: Methodsmentioning
confidence: 99%